The psychology of marketing : cross-cultural perspectives - Raab, Gerhard (Burlington, VT : Gower, 2010)
Market psychology in the context of systematics -- Theories of perception and social judgment formation as starting points -- The theory of social comparisons -- The theory of cognitive dissonance -- The theory of psychological reactance -- Attribution theories -- Cognitive response -- Theories of information processing.